Highly Efficient Solid-State Near-infrared Organic Light-Emitting Diodes incorporating A-D-A Dyes based on α,β-unsubstituted “BODIPY” Moieties - Andrea Zampetti (Nature Portfolio, 2017)
Abstract We take advantage of a recent breakthrough in the synthesis of α,β-unfunctionalised 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) moieties, which we symmetrically conjugate with oligothienyls in an unexpectedly stable form, and produce a “metal-free” A-D-A (acceptor-donor-acceptor) oligomer emitting in the near-infrared (NIR) thanks to delocalisation of the BODIPY low-lying lowest unoccupied molecular orbital (LUMO) over the oligothienyl moieties, as confirmed by density functional theory (DFT). We are able to retain a PL efficiency of 20% in the solid state (vs. 30% in dilute solutions) by incorporating such a dye in a wider gap polyfluorene matrix and demonstrate organic light-emitting diodes (OLEDs) emitting at 720 nm. We achieve external quantum efficiencies (EQEs) up to 1.1%, the highest value achieved so far by a “metal-free” NIR-OLED not intentionally benefitting from triplet-triplet annihilation. Our work demonstrates for the first time the promise of A-D-A type dyes for NIR OLEDs applications thereby paving the way for further optimisation.